Sharing Resources in Educational Communities - Littlejohn, Allison; Margarayn, Anoush (International Journal of Emerging Technologies in Learning (iJET), 2010)
The paper explores the implications of mobility within educational communities for sharing and reuse of educational resources. The study begins by exploring individualsâ?? existing strategies for sharing and reusing educational resources within localised and distributed communities, with particular emphasis on the impact of geographic location on these strategies. The results indicate that the geographic distribution of communities has little impact on individualsâ?? strategies for resource management, since many individuals are communicating via technology tools with colleagues within a localised setting. The study points to few major differences in the ways in which individuals within the localised and distributed communities store, share and collaborate around educational resources. Moving beyond the view of individuals being statically involved in one or two communities, mobility across communities, roles and geographic location are formulated and illustrated through eight scenarios. The effects of mobility across these scenarios are outlined and a framework for future research into mobility and resource sharing within communities discussed.